Studi Komparasi Modul Kimia Berbasis Media Screen Reader Jaws dan Braille Terhadap Prestasi, Motivasi, dan Kemandirian Belajar Peserta Didik Difabel Netra - Suprihatiningrum, Jamil; Fitriyani, Sholihah Nur (PLD UIN Sunan Kalijaga, 2014)
This study aimed to compare the achievement, motivation, and independent learning of blind students who use screen reader JAWS and braille module.This research was conducted at MAN Maguwoharjo Yogyakarta involving 5 blind students in the chemistry subject of academic year 2013/2014. One student is as an instrument validation test subject, two students as subjects in the experimental class and two students as subjects in the control class. The instruments used in this study are the observation sheet,multiple choice test, questionnaire responses, motivation scale, and independent learning scale. Data of student achievement, motivation and independence scale were analyzed using nonparametric statistical test of independent samples. The result shows that no significant difference between the achievement, motivation, and independence of blind students who use screen reader JAWS module and braille module.